The copper conundrum: elucidating the modes of copper antagonism in the rumen - Clarkson, A.H. (2020)
Copper is an essential trace element. In ruminants interactions occur during digestion which can interfere with copper absorption. Most notably, both iron and molybdenum in combination with sulphur. If there is insufficient copper available, thiomolybdate, formed from molybdenum and sulphur, can be absorbed and subsequently interfere with systemic copper function. It has not yet been established if copper-thiomolybdate is able to persist in the liver, or if the different copper sources participate differently in these interactions. The mode of action of the iron-sulphur pathway has also not been elucidated and very little is known about the nature of this interaction.